Apresentação (v. 3, n. 4, 2022) - Fonseca, Ricardo Marcelo; Guandalini Junior, Walter (História do Direito, 2022)
Apresentação - História do Direito: Revista do Instituto Brasileiro de História do Direito, v. 3, n. 4, 2022.